The interaction order - Denzin, Norman K. (Studies in symbolic interaction, 2019)
This volume brings together leading scholars in the area of symbolic interactionism to offer a broad discussion of issues including identity, dialogue and legitimacy. Authors move the concept of interaction order into new interpretive spaces, marking the unique contributions of symbolic interactionism to the contractions that define the postmodern social order.